PENGARUH PELATIHAN DAN KEPUASAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PERUM PEGADAIAN KANTOR WILAYAH PEKANBARU - Simamora, Fransisca; Restuti, Sri; ', Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the Perum Pengadaian Kanwil Pekanbaru is addressed at Jalan Sudirman 455 Pekanbaru. The purpose of this study was to determine the effect of education on morale and job satisfaction To determine the effect on employee morale at the Perum Pengadaian Kantor wilayah Pekanbaru. Population by Arikunto (2003: 129) defined as whole research subjects. While the sample part of the population that reflects all the characteristics possessed by the whole population. The population in question in this study were all employees Perum Pengadaian Kanwil Pekanbaru numbering as many as 103 people, and 51 of them sample. Hypothesis testing is done by t test and F test. Based on the research and discussion it is known that employee morale Perum Pengadaian Kanwil Pekanbaru has been good if the note of the work, absenteeism, employee turnover, employee demands, comfort in work and so forth. So also with the training program and the level of employee satisfaction. There is a significant effect of the training variables and job satisfaction on employee morale at the Perum Pengadaian Kanwil Pekanbaru either partially or simultaneously. There is a high contribution of variable training and job satisfaction on employee morale at the Perum Pengadaian Kanwil Pekanbaru which is seen from the coefficient of determination. There is a strong positive relationship anatara training variables and job satisfaction with employees' Perum Pengadaian Kanwil Pekanbaru which is evident from the correlation coefficient.Keywords: Morale, Education and Training, Job Satisfaction